Truth and reconciliation and other stories: a critical multimodal investigation of representations of post-apartheid South Africa in children's picturebooks: volume 1 - Smith, Jade (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2019)
Expected release date-April 2021
Keywords: Uncatalogued